The influence of regulation changes on the fluctuation of score of the beach volleyball games - Giatsis, Γιώργος; Zetou, Ελένη (Inquiries in Physical Education and Sport, 2003)
The purpose of this study was to investigate if the changes effected on the game of beach volleyball by the enforcement of the new scoring rules, influenced the fluctuation of score of the game. It recorded the total match duration and the number of sets, of 149 Greek games (ΕΠ98), 302 FIVB games (WS98) of 1998 period and 114 Greek games and 308 FIVB games of 2001 period. The period of 1998 the tournaments were played with “side out, on 15 point” scoring system and the period of 2001 with the “rally point, on 21 point” scoring system (only “tiebreak set” on 15 point). The results indicated that on “15 point” Greek games, the 16% ended with the difference of two points, the losers had mean score 9 points (sd=3.37) and in FIVB games with 12.3% respectively and mean score 8.40 (sd=3,46) points. After the changes of scoring system the 34.9% of Greek games and the 35.2% of FIVB2001 respectively, ended on 2-1 set, the 28.1% of sets ended with the difference of two points, although the 59% of games had sets with this difference of two points. Totally the 50% of games had sets with difference two points and the 35% of sets ended with the difference of two points. These results were shown that the games were done more interesting about 20-25%, while if considered that one interesting set could characterize an interesting game, this percentage increased about 40-45%. Finally these changes of scoring system will lead to beach volleyball games, which are both entertaining and fascinating to watch both on the court and on TV, to be more qualitative, more wavering and more interesting to the gallery.